Nanoparticles assisted drug delivery for effective management of Glioblastoma - Mansi Damani; Nagesh Nilawar; Munira Momin; Raghumani Singh Ningthoujham; Tabassum Khan (Next Nanotechnology)
Glioblastoma multiforme (GBM) is one of the most aggressive forms of primary brain tumor with a dire prognosis due to its heterogeneity, invasive nature, and resistance to conventional therapies. Standard treatments, including surgery, radiotherapy, and chemotherapy with temozolomide (TMZ), are often limited by the ability of the tumor to circumvent therapeutic effects and by the physiological barriers that restrict drug delivery to the brain parenchyma. Specifically, the blood-brain barrier (BBB) and the blood-brain tumor barrier (BBTB) impede the effective concentration of therapeutic agents within the brain, posing a significant challenge in treating GBM. The primary focus of current research has pivoted towards nanotechnology to address these limitations. Due to their size, surface modifications, and capability to encapsulate drugs, nanocarriers like polymeric, metallic, and lipid nanoparticles have shown potential in enhancing the penetration of anticancer agents across the BBB and BBTB, thus increasing treatment efficacy and minimizing general toxicity. Moreover, lipid-based nanoparticles, such as solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs), offer advantages in drug encapsulation, stability, and controlled release metal nanoparticles, including gold and silver nanoparticles, provide unique properties for imaging and photothermal therapy, potentially augmenting the efficacy of conventional treatments. This review elucidates the mechanisms by which nanocarriers cross the BBB and BBTB, emphasizing the importance of physicochemical properties such as size, charge, and surface functionality. The integration of nanotechnology in GBM treatment highlights the potential for nanoparticles to revolutionize drug delivery systems, overcoming the inherent challenges posed by the BBB and the tumor microenvironment. The promise of nanomedicine advances in this field could lead to more effective therapeutic strategies, significantly impacting patient outcomes in GBM management.